First report of the genus Physaloptera (Nematoda: Physalopteridae) in Lithobates montezumae (Anura: Ranidae) from Mexico (2014)
Nematode third stage larvae of the genus Physaloptera (Nematoda: Physalopteridae) were recovered from the stomach of Lithobates montezumae (Anura: Ranidae) collected in the Pedregal de San Angel Ecological Reserve in Mexico D. F. (19º11'6.50" N, 99º11'41.42" W; 2 312 m asl). The morphology of the larvae is briefly described and a list of previously recorded localities and hosts in Mexico is given. This study is the first record of Physaloptera sp. parasitizing L. montezumae, and also represents the first helminthological record for anurans in this locality, as well as a new locality record for the nematode genus.